α-Mangostin Alleviated Inflammation in Rats With Adjuvant-Induced Arthritis by Disrupting Adipocytes-Mediated Metabolism-Immune Feedback - Hu, Ying-Hao; Han, Jun; Wang, Lin; Shi, Chao; Li, Yan; Olatunji, Opeyemi Joshua; Wang, Xiu; Zuo, Jian (Frontiers in Pharmacology, 2021)
A previously identified anti-rheumatic compound α-mangostin (MAN) possesses notable metabolism regulatory properties. In this study, we investigate the immune implication of MAN-altered fat metabolism on adjuvant-induced arthritis (AIA) in rats. Seven days after AIA induction, the rats received oral treatment of MAN at 50 mg/kg/day for 30 days. Metabolic indicators and basic clinical parameters were evaluated using samples collected on day 20 and 38 after sacrifice. Expression of nicotinamide phosphoribosyltransferase (NAMPT), sirtuin 1 (SIRT1), peroxisome proliferator activated receptor gamma (PPAR-γ), stearoyl-coa desaturase 1 (SCD-1), toll like receptor 4 (TLR4), prostaglandin-endoperoxide synthase 2 (COX-2), (p)-JNK, (p)-p65 and IL-1β were investigated by either RT-qPCR or immunobloting methods. In in vitro experiments, we treated (pre)-adipocytes with monocytes/macrophages and MAN, and investigated the changes of macrophages brought by pre-adipocytes co-culture. Generally, MAN restored the impaired fat anabolism in AIA rats, indicated by increased fat reservoir, leptin and adiponectin secretion, and PPAR-γ and SCD-1 expression. Meanwhile, it decreased circulating IL-1β and IL-6 levels, restored serological lipid profile changes, and relieved oxidative stresses, demonstrating potent therapeutic effects on AIA. AIA rats-derived monocytes inhibited mRNA PPAR-γ and SCD-1 expression in pre-adipocytes. Contrary, MAN facilitated adipocyte differentiation in vitro, and increased free fatty acids production. It also significantly increased PPAR-γ and SCD-1 expression, which can be abrogated by PPAR-γ inhibitor T0070907. Similarly, lipopolysaccharide-primed macrophages inhibited PPAR-γ expression in the co-cultured pre-adipocytes, which was reversed by MAN. In the same co-culture system, lipopolysaccharide-induced inflammation was amplified by the co-existence of pre-adipocytes. More secretion of IL-1β and IL-6 and higher levels expression of COX-2, p-JNK, p-p65 and TLR4 were observed in lipopolysaccharide-treated macrophages when co-cultured by pre-adipocytes. The intensified inflammatory situation was eased by MAN. The treatment with pre-adipocytes culture medium achieved similar effects. Medium from lipopolysaccharide-treated adipocytes promoted IL-1β, IL-6 and MCP-1 production in separately cultured macrophages, and COX-2, p-JNK, p-p65 and TLR4 expression were increased at the meantime. MAN treatment on pre-adipocytes impaired these changes. It suggests that fat anabolism in AIA rats was deficient due to increased energy expenditure caused by inflammatory conditions. MAN restored fat metabolism homeostasis by up-regulating PPAR-γ, and reshaped secretion profile of adipocytes.